RETRACTED ARTICLE: CKS2 induces autophagy-mediated glutathione metabolic reprogramming to facilitate ferroptosis resistance in colon cancer - Leilei Yang; Chengfeng Fang; Jiaju Han; Yufeng Ren; Zaiping Yang; Lingyan Shen; Dinghai Luo; Ruili Zhang; Yan Chen; Shenkang Zhou (Molecular Medicine)
Abstract Background Ferroptosis, a form of cell death characterized by lipid peroxidation, plays a crucial role in tumor suppression, offering novel avenues for cancer therapy. Previous studies have indicated that high levels of cyclin-dependent kinase subunit 2 (CKS2) promote the progression of various cancers. However, the potential interplay between CKS2 and ferroptosis in colon cancer (CC) remains unclear. Methods Bioinformatics and RNA-seq analyses were employed to study genes associated with the ferroptosis signaling pathway. CKS2 expression was evaluated using quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot (WB). The in vitro and in vivo effects of CKS2 on CC cells were assessed through the CCK-8 assay, colony formation assay, propidium iodide (PI) staining, BODIPY staining, DCFH-DA staining, and animal experiments. Additionally, the impact of CKS2 on autophagy and glutathione (GSH) metabolism was investigated using a transmission electron microscope (TEM), immunofluorescence (IF) assays, WB experiments, and relevant assay kits. Results CKS2 expression was elevated in CC, indicating a poor clinical outcome. Knockdown of CKS2 significantly enhanced Erastin-induced ferroptosis in CC cells, leading to reduced GSH metabolism. Conversely, CKS2 overexpression produced opposite effects. Mechanistically, CKS2-induced autophagy reinforced GSH metabolism, thereby increasing resistance to ferroptosis in CC cells. Furthermore, inhibiting CKS2 promoted tumor ferroptosis by downregulating GPX4 expression. Additionally, CKS2 knockdown effectively increased sorafenib-induced ferroptosis both in vitro and in vivo. Conclusion CKS2 suppresses ferroptosis in CC by modulating GSH metabolism in both in vitro and in vivo settings. These findings offer new insights into targeting CKS2 for CC treatment and shed light on the mechanism of ferroptosis in CC.